Immigration and Health Services: Immigrant Complaint Patterns Regarding the Primary Health Care System in Israel - Shavit, Maya; Weisberg, Pnina; Gal, Iddo; Doron, Israel (Journal of immigrant & refugee studies, 2009)
Complaints are a potentially important source of information regarding health care quality in societies which face constant immigration. The purpose of this study was to examine the prevalence and patterns of complaints about health services from immigrants who are clients of Health Maintenance Organizations (HMOs) in Israel, to compare them with the complaint patterns of other Israelis, and to examine the contribution of sociodemographic variables to this comparison. Primary data were collected from the pooled responses of subjects who participated in two national phone surveys conducted in 2005 and 2007. The responses of 375 persons who immigrated to Israel after 1989 were compared to those of 824 persons who had immigrated earlier or were born in Israel. All respondents were screened for having had a reason to complain against their HMO. Respondents reported on whether they complained the pattern of their complaint, their awareness of their rights, and other socioeconomic characteristics. Of the immigrants who reported having a grievance, 19% of immigrants (as compared to 35% of other Israelis) had actually complained. Structural problems, such as payments, administrative matters, etc., were the most prevalent reasons for complaining. The main reasons for not complaining were lack of motivation and/or knowledge about the complaint process. In logistic regression analysis, immigration status, age, and income were significantly associated with making a complaint.